In vitro susceptibility pattern of Rhodococcus equi isolated from patients to antimicrobials recommended exclusively to humans, to domestic animals and to both - Ribeiro, Nícolas Garcia; da Silva, Paulo; de Lima Paz, Patrick Júnior [UNESP]; Filho, Marcelo Fagali Arabe [UNESP]; Listoni, Fernando Paganini [UNESP]; Listoni, Evandro Paganini [UNESP]; Panegossi, Letícia Colin [UNESP]; Ribeiro, Márcio Garcia [UNESP] (FapUNIFESP (SciELO), 2025)
Rhodococcus equi is an opportunistic soil-borne bacterium that is eliminated in feces of multi-host animals. An increase in multidrug-resistant R. equi isolates has been reported in humans and domestic animals, and it has been hypothesized that the treatment of R. equi in foals could increase the selective pressure on multidrug-resistant isolates and favor human infections by resistant isolates. We investigated the in vitro antimicrobial susceptibility/ resistance of 41 R. equi strains from humans, which were isolated from patients with pulmonary signs, using 19 antimicrobials from 10 distinct classes, recommended exclusively to humans, recommended exclusively to domestic animals and used in both. All isolates were subjected to mass spectrometry and identified as R. equi. Among the antimicrobials used exclusively in humans, tigecycline and vancomycin showed 100% efficacy. Amikacin, amoxicillin/clavulanic acid, imipenem, levofloxacin, clarithromycin, rifampin, ciprofloxacin, and gentamicin, used in both humans and animals, revealed high efficacy (97–100%). Conversely, a higher frequency of isolates was resistant to penicillin (87.8%) and trimethoprim/sulfamethoxazole (43.9%), which are used in both humans and animals. Among the antimicrobials used only in animals, isolates were resistant to florfenicol (46.4%), ceftiofur (17.1%), and enrofloxacin (2.5%). Multidrug resistance was observed in 34% of isolates. The identification of drug-resistant R. equi isolated from humans used exclusively in animals is circumstantial evidence of the pathogen transmission from domestic animals to humans. This study contributes to the molecular identification of Rhodococcus species from humans and to the epidemiological vigilance of the multidrug-resistant isolates.
Keywords: Human rhodococcosis; MALDI-TOF MS; Molecular diagnosis; Multidrug-resistant bacteria